Negative effects of the COVID-19 pandemic on physical activity and binge eating disorder in Brazilian women: a cross-sectional study - Caroline Pereira Garcês; Luciana Oliveira e Silva; Sara Menezes Nunes; Guilherme Morais Puga; Nadia Carla Cheik (Revista Brasileira de Ciências do Esporte, 2023)
ABSTRACT This study aimed to identify changes in physical activity, sitting time, and binge eating disorder in Brazilian women during the COVID-19 pandemic. A cross-sectional and retrospective study was conducted online on 150 Brazilian women adults. The prevalence of binge eating and physically inactive women increased during the COVID-19 pandemic (p = < 0.001 and p = 0.01, respectively). Binge eating was associated with insufficient physical activity before (p = 0.01) and during the pandemic (p = 0.05). The physical activity time and sitting time showed no differences after adjustment for possible confounders (p > 0.05). In conclusion, the pandemic affected Brazilian women’s lifestyle and eating behavior.